KEYS TO AN INTERMEDIATE COURSE IN ENGLISH FOR COMPUTING - Carbonell Olivares, María (Universitat Politècnica de València, 2011)
Keys to 'An Intermediate Course in English for Computing' provides the answer key to the textbook An Intermediate Course in English for Computing, also published by Editorial Universidad Politécnica de Valencia. This booklet is aimed at students using the above mentioned textbook who wish to work on the course material on their own. It may also be used to complement classroom work, assisting students in their private study of some of the activities included in the textbook, in a more autonomous approach to learning. This booklet is organized in two sections. The first one presents the solutions to the tasks in "Reading Practice" units, while the second part includes the keys to tasks in "Language Practice" units.